Study on Global Status of Solar Energy (International Journal of Food and Nutritional Sciences, 2022)
Solar energy is solar radiation that may produce heat, cause chemical processes, or generate electricity. The establishment limit of sustainable electricity on the world is steadily expanding. In recent years, inexhaustible electric energy demand has grown by an average of 30% per year, despite rapidly reducing expenditures and prices. Many public objectives are for percentages of electricity production, often 5–30%, but ranging from 2% to 90%. More than 66 percent of the 85 countries with public objectives in place by mid-2010 were concentrating on 2020 or the past in some fashion. Nonindustrial countries may achieve carbon neutrality by 2025 and reduce CO2 emissions afterwards, while concurrently increasing energy consumption due to economic expansion. This study presents an overview of current advancements in renewable energy such as photovoltaic PV, concentrated solar thermal power, and solar thermal heating and cooling, against this context. The globe is gradually evolving toward a more ecologically friendly energy source.